Influence of bias voltage on the hardness and toughness of CrAlN coatings via magnetron sputtering - Lee, Jyh-Wei (2013)
Chromium aluminum nitride (CrAlN) coatings were prepared via magnetron sputtering in a mixed Ar and N2 ambient. The effect of negative bias voltage (Vb) on the microstructure was investigated using a spectrum of characterizing techniques in terms of Glancing Angle X-ray Diffractometry, Field Emission Scanning Electron Microscopy and Transmission Electron Microscopy. As Vb increased from 50 to 260 V, hardness was improved from 10 to 26 GPa. Toughness grew at the same time and maximized at around 2 MPa·m1/2 when Vb = 210 V. Simultaneous improvements in hardness and toughness were attributed to the densified microstructure with refined grains and increased compressive stress.